2006
DOI: 10.1075/arcl.4.05bro
|View full text |Cite
|
Sign up to set email alerts
|

The construal of simultaneity in English with special reference to as-clauses

Abstract: This paper investigates how simultaneity between two events, a main clause event and a subordinate clause event, is coded in English. It focuses on as-clauses but also contrasts them with while-clauses. It argues that as-clauses evoke path events, i.e. events susceptible to change. It also points out that as-clauses define a family resemblance network in that different, though related, variants can be recognised. While-clauses are argued to generally evoke larger and more stable temporal configurations, e.g. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Previous studies have identified these parameters as being particularly important in differentiating simultaneity constructions in PDE; see e.g. Broccias (2006a, 2006b and 2008) and Silva (1991). As my Sister and I were sitting one day in a Grotto at the End of a Parterre, we saw the Marquis de Stainville and another Gentleman coming towards us.…”
Section: Data Extraction Selection and Annotationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have identified these parameters as being particularly important in differentiating simultaneity constructions in PDE; see e.g. Broccias (2006a, 2006b and 2008) and Silva (1991). As my Sister and I were sitting one day in a Grotto at the End of a Parterre, we saw the Marquis de Stainville and another Gentleman coming towards us.…”
Section: Data Extraction Selection and Annotationmentioning
confidence: 99%
“…sigh , smile ); ‘mental’, which refers to cognitive processes; ‘be’, which includes not only the verb be but also stative verbs of posture (such as sit in (4)), and a handful of minor types. (We have refrained from offering a detailed breakdown of all the classes because, for example, the percentages for non-change verbs in as -clauses are relatively low; see also Broccias 2006a.) Punctuality is meant to specify whether the main clause or the temporal clause (or both) depicts events of relatively short or relatively long duration.…”
Section: Data Extraction Selection and Annotationmentioning
confidence: 99%
See 3 more Smart Citations